Knowledge science, engineering and management : 9th International Conference, KSEM 2016, Passau, Germany, October 5-7, 2016, Proceedings /: 9th International Conference, KSEM 2016, Passau, Germany, October 5-7, 2016, Proceedings. (2016) - Unknown
No abstract available